2021
DOI: 10.1007/s11938-021-00342-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Barrett’s Oesophagus: Are We Ready for it?

Abstract: Purpose of review The targeted approach adopted for Barrett’s oesophagus (BO) screening is sub-optimal considering the large proportion of BO cases that are currently missed. We reviewed the literature highlighting recent technological advancements in efforts to counteract this challenge. We also provided insights into strategies that can improve the outcomes from current BO screening practises. Recent findings The standard method for BO detection, endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…30 Furthermore, if these risk stratification tools are coupled with emerging novel screening modalities that do not require sedation, it may be possible to offer cost-effective BE screening to more patients. 16 For example, a recent randomized control trial demonstrated that a BE screening program based on the cell collection device cytosponge trefoil factor 3 identified 10 times more cases of BE compared to usual care in general practices in the United Kingdom. 31 This study has several strengths that lend credibility to its conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, if these risk stratification tools are coupled with emerging novel screening modalities that do not require sedation, it may be possible to offer cost-effective BE screening to more patients. 16 For example, a recent randomized control trial demonstrated that a BE screening program based on the cell collection device cytosponge trefoil factor 3 identified 10 times more cases of BE compared to usual care in general practices in the United Kingdom. 31 This study has several strengths that lend credibility to its conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These include upper endoscopy risk stratification algorithms and nonendoscopic BE screening modalities, such as minimally invasive cell collection devices, unsedated transnasal endoscopy, and exhaled volatile organic acids. [14][15][16] As 40% of patients with EAC present at a distant stage, which has a survival rate 9 times worse than that of localized EAC, 1 these novel BE screening strategies have the potential to vastly improve the morbidity and mortality of EAC by inducing a stage shift. As PCPs are often the first practitioners to diagnose and manage GERD, understanding their current practice patterns may provide key insights about knowledge, attitudes, and barriers to BE screening that could guide the development and implementation of future BE screening programs.…”
Section: Introductionmentioning
confidence: 99%
“…The Cytosponge (Medtronic, Minneapolis, MN, Figure 4 ) is a 30 mm polyurethane sponge, compressed withing a gelatin capsule and attached to a string[ 13 ]. Once patient swallows the capsule and it reaches the stomach, the capsule opens up and reveals the sponge.…”
Section: Cell Collection Devices With Biomarkersmentioning
confidence: 99%
“…EsoCheck (Lucid Diagnostics, New York, NY, Figure 6 ) is a balloon-based sampling device which consists of a collapsible balloon attached to thin silicone catheter connected to a syringe[ 13 ]. Once EsoCheck is swallowed and is in the stomach, the balloon is inflated by injecting air into the catheter and withdrawn through the distal 3-6 cm of the esophagus, collecting epithelial cells.…”
Section: Cell Collection Devices With Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation